Orang NTT: Diaspora Communities and Multiculturalism in Bali - Sunaryo, Fransiska Dewi Setiowati (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
The cultural interaction of Orang NTT with local communities in Bali has implications for forming a multicultural society. Although there have been previous studies on migration and ethnicity, few have examined East Nusa Tenggara ethnicity in the Bali region. This research aims to understand the cultural interaction between Orang NTT and local communities in Bali and how they contribute to the social harmony and the formation of a multicultural society in Bali. This qualitative research was conducted in Denpasar City (the center of the government) and Badung Regency (the center of tourism) in Bali. I combined observation and in-depth interviews as my data collection methods. Ten informants were interviewed: seven Orang NTT, two Balinese, two Flobamora community leaders, a Christian religious leader, and an entrepreneur. The study shows that push and pull factors influence how Orang NTT migrate to Bali. While the push factors include the economic and educational conditions in NTT and the attractiveness offered by Bali as a destination for NTT migration; pull factors comprise better economic opportunities, better access to education, and better life opportunities. In addition, Orang NTT in Bali plays an important role in strengthening cultural diversity and social harmony in the local community. These findings have important implications for society's understanding of social integration and how minority groups contribute to forming a harmonious multicultural society. The study contributes to the understanding on how Orang NTT migrate from the eastern region to Bali, while providing new insights into how social and cultural interactions can shape multicultural identity in a region. This can serve as a basis for the development of local policies related to diversity and as a reference for studies on diaspora and the formation of multicultural communities in other regions.